Odpowiedzi

2010-02-16T16:16:56+01:00
A) 5x+10y=5 (x+2y)
b) 4m+4 =4 (m+1)
c) 3a-3 = 3 (a-1)
d) 5xy-x = x(5y-1)
e) -6a²-2a = -2a(3a+1)
f) 6a²-12ab = 6a(a -2b)
g) 2xyz-4x²y²z+xyz² = xyz (2 - 4ay +z)
h) stv²-stv+tv² = tv (sv -s +t)
3 3 3
  • Użytkownik Zadane
2010-02-16T16:18:38+01:00
A) 5x + 10y = 5 (x + 2y)
b) 4m + 4 = 4 (m + 1)
c) 3a - 3 = 3 (a - 1)
d) 5xy - x = x (5y - 1)
e) -6a²-2a = -2a (3a + 1)
f) 6a²-12ab = 6a(a -2b)
g) 2xyz - 4x²y²z + xyz² = xyz (2 - 4ay +z)
h) stv² - stv + tv² = tv (sv - s +t)
1 1 1
2010-02-16T16:25:35+01:00
A. 5(x+2y)
b. 4(m+1)
c. 3(a-1)
e. 2a(-3a-1)
f. 6a(a-2b)
g. xyz(2-4xyz+z)
h. tv(sv-1+v)
1 1 1